Interindividual variability in response to protein and fish oil supplementation in older adults: a randomized controlled trial. Issue 2 (21st February 2022) - Murphy, Caoileann H.; Connolly, Claire; Flanagan, Ellen M.; Mitchelson, Kathleen A.J.; de Marco Castro, Elena; Egan, Brendan; Brennan, Lorraine; Roche, Helen M.
Abstract: Background: Precision nutrition is highly topical. However, no studies have explored the interindividual variability in response to nutrition interventions for sarcopenia. The purpose of this study was to determine the magnitude of interindividual variability in response to two nutrition supplementation interventions for sarcopenia and metabolic health, after accounting for sources of variability not attributable to supplementation. Methods: A 24 week, randomized, double‐blind, placebo‐controlled trial tested the impact of leucine‐enriched protein (LEU‐PRO), LEU‐PRO plus long‐chain n ‐3 PUFA (LEU‐PRO+ n ‐3) or control (CON) supplementation in older adults ( n  = 83, 71 ± 6 years) at risk of sarcopenia. To estimate the true interindividual variability in response to supplementation (free of the variability due to measurement error and within‐subject variation), the standard deviation of individual responses (SDR ) was computed and compared with the minimally clinically important difference (MCID) for appendicular lean mass (ALM), leg strength, timed up‐and‐go (TUG), and serum triacylglycerol (TG) concentration. Clinically meaningful interindividual variability in response to supplementation was deemed to be present when the SDR positively exceeded the MCID. The probability that individual responses were clinically meaningful, and the phenotypic, dietary, and behavioural determinants of response to supplementation were examined. Results: The SDR was below the MCID for ALM (LEU‐PRO: −0.12 kg [90% CI: −0.38, 0.35], LEU‐PRO+ n ‐3: −0.32 kg [−0.45, 0.03], MCID: 0.21 kg), TUG (LEU‐PRO: 0.58 s [0.18, 0.80], LEU‐PRO+ n ‐3: 0.73 s [0.41, 0.95], MCID: 0.9 s) and TG (LEU‐PRO: −0.38 mmol/L [−0.80, 0.25], LEU‐PRO+ n ‐3: −0.44 mmol/L [−0.63, 0.06], MCID: 0.1 mmol/L), indicating no meaningful interindividual variability in response to either supplement. The SDR exceeded the MCID (19 Nm) for strength in response to LEU‐PRO (25 Nm [−29, 45]) and LEU‐PRO+ n ‐3 (23 Nm [−29, 43]) supplementation but the effect was uncertain, evidenced by wide confidence intervals. In the next stage of analysis, similar proportions of participant responses were identified as very likely, likely, possibly, unlikely, and very unlikely to represent clinically meaningful improvements across the LEU‐PRO, LEU‐PRO+ n ‐3, and CON groups ( P  > 0.05). Baseline LC n ‐3 PUFA status, habitual protein intake, and numerous other phenotypic and behavioural factors were not determinants of response to LEU‐PRO or LEU‐PRO+ n ‐3 supplementation. Conclusions: Applying a novel, robust methodological approach to precision nutrition, we show that there was minimal interindividual variability in changes in ALM, muscle function, and TG in response to LEU‐PRO and LEU‐PRO+ n ‐3 supplementation in older adults at risk of sarcopenia.